INTEGRASI PROGRAM EDUKASI LITERASI, PEMBERDAYAAN SOSIAL, DAN PARTISIPASI PEMBANGUNAN DALAM KEGIATAN KULIAH PENGABDIAN MASYARAKAT DI DESA BUMI NABUNG ILIR - Ely Elsa; Yuyun Yunita; Dicki Mahendra; Ega Aurani Shafa; Dwi Indriyani; Dwi Febrianti; Dewi Ngainun Luthfiya; Siti Zuleha; Datun Nurhasanah (LPPI UMN AL WASHLIYAH, 2026)
Community service activities represent one of the implementations of the Tri Dharma of higher education, aimed at providing tangible contributions to society. This program was conducted in Bumi Nabung Ilir Village, focusing on improving educational literacy, financial literacy, digital literacy, and social awareness within the community. The program was motivated by several issues, including low literacy and numeracy skills among elementary students, limited understanding of financial literacy from an early age, insufficient awareness among adolescents in using digital media wisely, and a lack of reproductive health education for young women. Additionally, village development was supported through the construction of a hamlet monument as a regional identity. The activities were carried out using a participatory approach, including field observations, socialization, counseling, tutoring, practical activities, and the development of village facilities. The target groups included elementary and junior high school students, village youth, and the local community. The results indicate that the program had a positive impact, such as improved literacy and numeracy skills, increased awareness of saving from an early age, better understanding of responsible digital media use among adolescents, and enhanced knowledge of reproductive health among young women. The construction of the hamlet monument also strengthened regional identity and encouraged community participation in village development. Overall, this program demonstrates that collaboration between university students, educational institutions, and the community can effectively enhance educational quality and social awareness.